IMPORTANCE OF INNOVATIVE EDUCATIONAL METHODS IN TEACHING FOREIGN LANGUAGES - Khikmatullayeva Durdona; Yusupov Asror Raimqul o'g'li (Лучшие интеллектуальные исследования, 2023)
Annotation: This article deals with the ways of using different communicative games in teaching foreign languages to young learners. As young children are very imaginative and learn more if they are enjoying what they are doing, communicative games for them are considered a very effective way of learning a foreign language.